Membrane electrode based on composite diaphragm, preparation method of membrane electrode and application of membrane electrode in alkaline electrolyzed water system

By using a composite separator with a raised-concave structure in the alkaline electrolytic water hydrogen production system and directly coating the catalyst layer, the problem of catalyst layer falling off is solved, the stability and electrolytic efficiency of the electrode are improved, and a lower energy consumption and a more compact electrolytic system is achieved.

CN119615221APending Publication Date: 2025-03-14华能张掖能源有限公司 +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510087817.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-20
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

In the alkaline electrolytic water hydrogen production system, it is difficult for the prior art to achieve the close bond between the cathode/anode catalyst and the film material, resulting in the catalyst layer being easily shedded during the diaphragm vibration caused by electrolyte erosion, affecting the stability and electrolytic efficiency of the electrode.

Method used

A composite separator with a raised-concave structure is used as the film electrode, and the catalyst layer is directly coated on the surface of the composite separator to form a zero gap structure. The raised-concave structure not only improves the stability of the catalyst layer, but also increases the surface area of ​​the electrode and reduces energy consumption and voltage loss.

Benefits of technology

By directly coating the catalyst layer, the stability and electrolytic efficiency of the membrane electrode are improved, energy consumption and voltage loss are reduced, and a more compact electrolytic system structure is allowed to be obtained, improving the safety of electrolytics.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119615221A_ABST
    Figure CN119615221A_ABST
Patent Text Reader

Abstract

The invention relates to a membrane electrode based on a composite diaphragm, a preparation method of the membrane electrode and application of the membrane electrode in an alkaline water electrolysis system. Specifically, the invention relates to a membrane electrode based on a composite diaphragm, comprising: a composite diaphragm; a first catalyst layer; and a second catalyst layer; wherein the composite diaphragm is provided with a substrate layer and a surface layer, the surface layer is provided with a convex-concave structure, and the first catalyst layer and the second catalyst layer are uniformly coated on the surface layer of the composite diaphragm.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of hydrogen production by water electrolysis, and in particular relates to a membrane electrode based on a composite diaphragm, a preparation method thereof and an application thereof in an alkaline water electrolysis system. Background Art

[0002] Water electrolysis is an industrial-scale hydrogen production method that converts electrical energy into chemical energy and produces hydrogen and oxygen by electrolyzing water molecules. Common water electrolysis methods include: alkaline water electrolysis (ALK), which uses KOH or NaOH aqueous solution as the electrolyte, produces oxygen at the anode and hydrogen at the cathode. The technology is mature, low-cost, and easy to operate, but there are problems such as large volume and weight, and corrosiveness of alkali solution. The diaphragm is one of the key components of the alkaline electrolysis cell, which is used to separate hydrogen and oxygen to prevent mixing. Proton exchange membrane water electrolysis (PEM): It uses solid polymer electrolytes and has the advantages of high current density, high hydrogen purity, and compact equipment. In addition, it can be started and stopped flexibly and quickly, and has strong adaptability to renewable energy power input, but the equipment cost is high and the service life is relatively short. Solid oxide water electrolysis (SOEC): It operates at high temperature and has higher hydrogen production efficiency, but high temperature also limits its promotion and application. It is still in the initial demonstration stage. Anion exchange membrane electrolysis of water to produce hydrogen (AEM): Its advantage is that it avoids the use of precious metal catalysts and is compatible with low-concentration electrolytes, but it is still in the early demonstration stage and the technology is not yet mature.

[0003] Among these common water electrolysis methods, alkaline water electrolysis (ALK) technology is a mature and widely used one. Under the action of direct current, water molecules undergo a reduction reaction at the cathode to generate hydrogen and hydroxide ions (OH-), and the hydroxide ions pass through the diaphragm to the anode, where they undergo an oxidation reaction to generate oxygen and water. A high concentration (20% to 30%) KOH solution is usually used as an electrolyte to increase ionic conductivity. NaOH and NaCl solutions can also be used as electrolytes. In the ALK method, the anode usually uses a high specific surface area nickel-plated steel plate or nickel-copper-iron as a catalyst and loads manganese, tungsten and ruthenium oxides; the cathode uses steel plated with high specific surface area nickel or nickel-cobalt alloy as a catalyst. There is a diaphragm between the anode and the cathode to prevent the mixing of hydrogen and oxygen while allowing the electrolyte to pass through. The ALK method usually operates at a temperature of 60 to 80°C, has an electrolysis efficiency of 59% to 70%, and the hydrogen purity can reach 99.5% to 99.9998%. The ALK method occupies an important position in industrial applications due to its maturity, low cost and reliability, but it faces some challenges, such as increasing current density, reducing gas cross-mixing and improving dynamic response speed. In particular, in the system of the ALK method, the nickel-based electrodes coated with catalysts are separated by a porous diaphragm. In order to reduce the electrolysis voltage, the two electrodes need to fit the diaphragm as closely as possible to reduce the solution resistance between the two, and ultimately achieve the purpose of reducing the power consumption of hydrogen production. However, due to the limitations of electrolyzer assembly and component dimensional accuracy, the true "zero gap" configuration of the two electrodes is difficult to achieve. In addition, drawing on other water electrolysis hydrogen production methods, such as anion exchange membrane water electrolysis hydrogen production, proton exchange membrane water electrolysis hydrogen production and solid oxide water electrolysis hydrogen production, the cathode / anode catalyst can be directly coated on the surface of the membrane material to achieve a close combination of the three, but in the alkaline water electrolysis hydrogen production system, the surface catalyst layer is easy to fall off under the action of the diaphragm vibration caused by the electrolyte flushing, so this structure has not yet been applied in actual production. Summary of the invention

[0004] Therefore, the main purpose of the present invention is to provide a membrane electrode based on a composite diaphragm, a preparation method thereof, and an application thereof in an alkaline water electrolysis system. Among them, the membrane electrode includes a composite diaphragm with a convex-concave structure, and the catalyst layer is directly coated on the surface of the composite diaphragm to form a zero-gap structure. Due to the convex-concave structure, the catalyst layer coated on the surface can be prevented from falling off during bending or shaking during the generation and use process, thereby improving the stability of the membrane electrode. At the same time, since the convex-concave structure increases the surface area of ​​the electrode, it is possible to improve the electrolysis efficiency, reduce energy consumption, increase the current density, and reduce voltage loss. On the other hand, due to the adhesion of the electrode to the diaphragm, the solution resistance between the two electrodes is greatly reduced, which not only allows a more compact structure to be obtained, but also further improves the high efficiency and safety of electrolysis.

[0005] In order to achieve the above-mentioned purpose, according to the first aspect of the present invention, the present invention provides a membrane electrode based on a composite diaphragm, comprising: a composite diaphragm; a first catalyst layer; and a second catalyst layer; wherein the composite diaphragm has a base layer and a surface layer, the surface layer has a convex-concave structure, and the first catalyst layer and the second catalyst layer are uniformly coated on the surface layer of the composite diaphragm.

[0006] Furthermore, the thickness of the base layer of the composite diaphragm is 250 to 400 μm, the base layer contains a polyphenylene sulfide support network, the thickness of the polyphenylene sulfide support network is 100 to 300 μm and the porosity is 50 to 150 meshes; the convex-concave structure of the surface layer of the composite diaphragm has a longitudinal cross-sectional shape selected from at least one of the following: continuous triangles, discontinuous triangles, discontinuous rectangles, continuous trapezoids, discontinuous trapezoids, continuous ellipses, discontinuous ellipses and any combination thereof; the convex-concave structure is distributed on the surface layer in regular lattice positions or in irregular random positions, preferably in regular lattice positions.

[0007] Further, the height of each continuous triangle is 10 to 100 μm, preferably 30 to 80 μm, more preferably 50 μm; the base is 10 to 100 μm, preferably 30 to 80 μm, more preferably 50 μm; the ratio of the height to the base is 1:2 to 2:1, preferably 1:1; the height of each non-continuous triangle is 10 to 100 μm, preferably 30 to 80 μm, more preferably 50 μm; the base is 10 to 100 μm, preferably 30 to 80 μm, more preferably 50 μm; the ratio of the height to the base is 1:2 to 2:1, preferably 1:1; the distance between two adjacent triangles is 1 0-100 μm, preferably 30-80 μm, more preferably 50 μm; the height of each non-continuous rectangle is 10-100 μm, preferably 30-80 μm, more preferably 50 μm; the width is 10-100 μm, preferably 30-80 μm, more preferably 50 μm; the ratio of height to width is 1:2-2:1, preferably 1:1; the height of each continuous trapezoid is 10-100 μm, preferably 30-80 μm, more preferably 50 μm; the upper base is 10-100 μm, preferably 20-80 μm, more preferably 30 μm, and the lower base is 10-100 μm, preferably 20-8 0μm, preferably 70μm, the ratio of height to bottom is 1:2 to 2:1, preferably 1:1; the height of each rectangle of the non-continuous trapezoid is 10 to 100μm, preferably 30 to 80μm, more preferably 50μm; the upper bottom is 10 to 100μm, preferably 20 to 80μm, more preferably 30μm, the lower bottom is 10 to 100μm, preferably 20 to 80μm, more preferably 70μm, the ratio of height to bottom is 1:2 to 2:1, preferably 1:1; the distance between two adjacent trapezoids is 10 to 100μm, preferably 30 to 80μm, more preferably 50μm; the short half of the continuous ellipse is 10 to 100μm, preferably 30 to 80μm, more preferably 50μm; the short half of the continuous ellipse is 10 to 100μm, preferably 20 to 80μm, more preferably 30μm; the short half of the continuous ellipse is 10 to 100μm, preferably 20 to 80μm, more preferably 70μm; the short half of the continuous ellipse is 10 to 100μm, preferably 30 to 80μm, more preferably 50μm; the short half of the continuous ellipse is 10 to 100μm, preferably 20 to 80μm, more preferably 3 ... The axis is 10-100 μm, preferably 30-80 μm, more preferably 50 μm; the major semi-axis is 10-100 μm, preferably 30-80 μm, more preferably 50 μm; the ratio of the minor semi-axis to the major semi-axis is 1:2-2:1; the minor semi-axis of the non-continuous ellipse is 10-100 μm, preferably 30-80 μm, more preferably 50 μm; the major semi-axis is 10-100 μm, preferably 30-80 μm, more preferably 50 μm; the ratio of the minor semi-axis to the major semi-axis is 1:2-2:1; the distance between two adjacent ellipses is 10-100 μm, preferably 30-80 μm, more preferably 50 μm.

[0008] Furthermore, the surface resistance of the composite diaphragm is 0.1 to 0.4 ohm cm 2 @25℃ 30wt% KOH, bubble point pressure is 2~10bar, hydrogen permeability is 1~25*10 –12mol / (cm sec bar); the first catalyst layer comprises a cathode catalyst, which is at least one selected from the following: platinum carbon, Raney nickel, nickel powder, cobalt powder, nickel molybdenum powder and nickel cobalt powder, preferably Raney nickel; and the second catalyst layer comprises an anode catalyst, which is at least one selected from the following: nickel hydroxide, cobalt hydroxide, iron hydroxide, nickel cobalt hydroxide, nickel iron hydroxide, cobalt iron hydroxide and nickel cobalt iron hydroxide, preferably nickel iron hydroxide; wherein the thickness of the first catalyst layer and the second catalyst layer is 10 to 30 μm.

[0009] Furthermore, the surface resistance of the composite diaphragm is 0.3 ohm cm 2 @25℃ 30wt% KOH, bubble point pressure is 3bar, hydrogen permeability is 20*10 –12 mol / (cm sec bar); the first catalyst layer is a Raney nickel layer with a thickness of 25 μm; and the second catalyst layer is a nickel iron hydroxide layer with a thickness of 15 μm.

[0010] According to a second aspect of the present invention, the present invention provides a method for preparing a membrane electrode according to the first aspect of the present invention, wherein the method comprises the following steps: (1) placing a substrate having a surface structure in a horizontal position, then placing a polyphenylene sulfide support mesh on the surface of the substrate, then coating the substrate with a composite membrane casting liquid to form a coated composite membrane casting liquid layer, the polyphenylene sulfide support mesh being immersed in the casting liquid layer, the first surface of the composite membrane casting liquid layer being in contact with the surface structure of the substrate to form a convex-concave structure, and the second surface opposite to the first surface being a plane; (2) immersing the substrate having the composite membrane casting liquid layer coated on the surface in step (1) in a first phase inversion solution to perform a first phase inversion for a first time; (3)

[0011] The same substrate as in step (1) is turned upside down on the second surface after the first phase transformation in step (2), and then mechanically squeezed to form a convex-concave structure on the second surface; (4) the two substrates in step (3) are removed to obtain a composite diaphragm embryo, and the composite diaphragm embryo is placed in a second phase transformation solution for a second phase transformation for a second time to obtain a composite diaphragm, and then the composite diaphragm is rinsed with pure water; (5) a first catalyst slurry and a second catalyst slurry are prepared, and the first catalyst slurry is evenly coated on the first surface of the composite diaphragm in step (4), and the second catalyst slurry is evenly coated on the second surface of the composite diaphragm in step (4), and then dried for a second time to obtain a membrane electrode.

[0012] Further, the thickness of the polyphenylene sulfide support mesh in step (1) is 100-300 μm and the porosity is 50-150 mesh, preferably the thickness of the polyphenylene sulfide support mesh is 200 μm and the porosity is 100 mesh; the material of the substrate in step (1) is a rigid material or a plastic material, preferably, the rigid material is at least one selected from the following: sapphire, quartz, nickel, titanium, stainless steel and copper; the plastic material is at least one selected from the following: polytetrafluoroethylene, polypropylene and polyethylene terephthalate; preferably, the material of the substrate is polytetrafluoroethylene; the coating in step (1) is performed by slit coating, and the gap of the slit is 200-1000 μm, preferably 300-800 μm, more preferably The thickness of the composite membrane is 400-700 μm, and the most preferred thickness is 500 μm; the width of the slit is 20-200 cm, and the most preferred thickness is 30-100 cm, and the most preferred thickness is 40-70 cm, and the most preferred thickness is 50 cm; the coating line speed is 100-1000 mm / min, and the most preferred thickness is 150-750 mm / min, and the most preferred thickness is 200 mm / min; and the coating flow rate is 10-100 mL / min, and the most preferred thickness is 15-50 mL / min, and the most preferred thickness is 15 mL / min; the viscosity of the composite membrane casting liquid in step (1) is 10-1000 mPa.s, and the most preferred thickness is 50-800 mPa.s, and the most preferred thickness is 100-500 mPa.s, and the most preferred thickness is 200 mPa.s.

[0013] Furthermore, the first phase inversion solution in step (2) is selected from any one of the following: water, ethanol, acetone, toluene, cyclohexene, ethylene glycol and chloroform, preferably pure water; the first phase inversion time in step (2) is 0.1 to 10 minutes, preferably 1 minute.

[0014] Furthermore, the mechanical extrusion pressure in step (3) is 0.1-1 MPa, preferably 0.15-0.5 MPa, and more preferably 0.2 MPa; the film thickness after extrusion is 100-500 μm, preferably 200-400 μm, and more preferably 300 μm.

[0015] Furthermore, the second phase conversion solution in step (4) is a mixed solution of an organic acid and an inorganic salt, the organic acid is at least one selected from the following: citric acid, fumaric acid, acetic acid, formic acid and tannic acid, preferably tannic acid or citric acid; the inorganic salt is at least one selected from the following: potassium sulfate, sodium sulfate, potassium nitrate, sodium nitrate, potassium chloride and sodium chloride, preferably sodium chloride or potassium chloride; the concentration of the organic acid is 0.001 to 1 mol / L, preferably 0.01 to 0.5 mol / L, more preferably 0.02 to 0.1 mol / L; the concentration of the inorganic salt is 0.01 to 1 mol / L, preferably 0.05 to 0.5 mol / L, more preferably 0.1 to 0.3 mol / L; the second time in step (4) is 5 to 120 min, preferably 30 to 90 min, more preferably 60 min; the pure water washing in step (4) is performed 1 to 5 times, preferably 3 times.

[0016] Further, the first catalyst slurry in step (5) comprises: (i) a cathode catalyst, which is at least one selected from the following: platinum carbon, Raney nickel, nickel powder, cobalt powder, nickel molybdenum powder and nickel cobalt powder, preferably Raney nickel; the content of the cathode catalyst is 1 to 100 mg / mL of the first catalyst slurry, preferably 10 to 80 mg / mL of the first catalyst slurry, more preferably 30 to 70 mg / mL of the first catalyst slurry, and most preferably 50 mg / mL of the first catalyst slurry; (ii) a dispersion, which is a mixture of ethanol and any one selected from the following in a volume ratio of 1:10 to 10:1: n-butanol, isopropanol, turpentine, ethylene dichloride, (iii) a viscosity modifier, which is an anion exchange resin, preferably any one selected from the following: polystyrene-based anion exchange resin, tetramethylammonium hydroxide-based resin, amino resin, polyvinyl chloride-based resin, more preferably amino resin; the amount of the viscosity modifier is 0.1-10wt% of the mass of the cathode catalyst, preferably 1-5wt%, more preferably 2wt%; the second catalyst slurry in step (5) comprises: (i) an anode catalyst, which is at least one selected from the following: nickel hydroxide, cobalt hydroxide, iron hydroxide, hydrogen hydroxide Nickel cobalt oxide, nickel iron hydroxide, cobalt iron hydroxide and nickel cobalt iron hydroxide, preferably nickel iron hydroxide; wherein the content of the anode catalyst is 1-100 mg / mL of the second catalyst slurry, preferably 10-80 mg / mL of the second catalyst slurry, more preferably 20-70 mg / mL of the first catalyst slurry, and most preferably 30 mg / mL of the second catalyst slurry; (ii) a dispersion liquid, which is a mixture of ethanol and any one selected from the following in a volume ratio of 1:10 to 10:1: n-butanol, isopropanol, turpentine, ethylene glycol, glycerol and tert-butanol, preferably a mixture of ethanol and isopropanol in a volume ratio of 2:1; and (i ii) a viscosity modifier, which is an anion exchange resin, preferably any one selected from the following: a polystyrene-based anion exchange resin, a tetramethylammonium hydroxide-based resin, an amino resin, a polyvinyl chloride-based resin, preferably an amino resin; the amount of the viscosity modifier is 0.1 to 10 wt % of the mass of the anode catalyst, preferably 1 to 5 wt %, more preferably 2 wt %; the viscosity of the first catalyst slurry in step (5) is 100 to 200 mPa.s, preferably 110 to 150 mPa.s, more preferably 120 mPa.s; the viscosity of the second catalyst slurry is 100 to 200 mPa.s; preferably 100 mPa.s; the gap of the slit coating in step (5) is 10-200 μm, preferably 20-100 μm, more preferably 50 μm; the width of the slit is 20-200 cm, preferably 30-100 cm, more preferably 40 cm; the linear speed is 50-200 mm / min, preferably 50 mm / min; the flow rate is 1-20 mL / min, preferably 5 mL / min; the drying in step (5) is carried out under a non-flowing inert gas environment, preferably the inert gas is at least one selected from the following: nitrogen, helium and argon, more preferably nitrogen; the humidity is 10-50% RH, preferably 25% RH; the drying temperature is 25-50°C, preferably 30-40°C, more preferably 37°C; the second time is 6-24h, preferably 12h. .

[0017] According to a third aspect of the present invention, the present invention provides a use of a membrane electrode according to the first aspect of the present invention in an alkaline water electrolysis system. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] The drawings constituting a part of the present application are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the drawings:

[0019] Figure 1 A flow chart of a method according to the invention is shown. DETAILED DESCRIPTION

[0020] The following description is presented to enable a person of ordinary skill in the art to obtain and use various embodiments. Descriptions of specific devices, techniques, and applications are provided only as examples. Various modifications to the examples described herein will be apparent to a person of ordinary skill in the art, and the general principles defined herein may be applied to other examples and applications without departing from the scope of the various embodiments. Therefore, the various embodiments are not intended to be limited to the examples described and illustrated herein, but are consistent with the scope of the claims. It should be noted that, in the absence of conflict, the embodiments in this application and the features in the embodiments may be combined with each other. The present invention will be described in detail below in conjunction with the embodiments.

[0021] As described in the background technology section, in an alkaline water electrolysis hydrogen production system, if the cathode / anode catalyst is directly coated on the surface of the membrane material, the surface catalyst layer is easily fallen off due to the vibration of the diaphragm caused by the scouring of the electrolyte. Therefore, the above structure has not been actually applied to the production system of alkaline water electrolysis hydrogen production.

[0022] Due to the above problems, it is necessary to provide a membrane electrode based on a composite diaphragm, wherein the membrane electrode includes a composite diaphragm with a convex-concave structure, and the catalyst layer is directly coated on the surface of the composite diaphragm to form a zero-gap structure. Due to the convex-concave structure, the catalyst layer coated on the surface can be prevented from falling off during bending or shaking during the production and use process, thereby improving the stability of the membrane electrode. At the same time, since the convex-concave structure increases the surface area of ​​the electrode, it can improve the electrolysis efficiency, reduce energy consumption, increase the current density, and reduce the voltage loss. On the other hand, since the electrode is fitted to the diaphragm, the solution resistance between the two electrodes is greatly reduced, which not only allows a more compact structure to be obtained, but also further improves the electrolysis efficiency and safety.

[0023] In order to achieve the above-mentioned purpose, in a typical embodiment, a membrane electrode based on a composite diaphragm includes: a composite diaphragm; a first catalyst layer; and a second catalyst layer; wherein the composite diaphragm has a base layer and a surface layer, the surface layer has a convex-concave structure, and the first catalyst layer and the second catalyst layer are uniformly coated on the surface layer of the composite diaphragm.

[0024] In one embodiment, the thickness of the substrate layer of the composite membrane is 250-400 μm, for example, 250, 260, 270, 280, 290, 300, 310, 320, 330, 340, 350, 360, 370, 380, 390 or 400 μm. The thickness of the substrate layer of the composite membrane should be sufficient to support the structural stability of the composite membrane to maintain its function. In one embodiment, the base layer contains a polyphenylene sulfide support mesh, the thickness of the polyphenylene sulfide support mesh is 100-300 μm, for example, 100, 110, 120, 130, 140, 150, 160, 170, 180, 190, 200, 210, 220, 230, 240, 250, 260, 270, 280, 290, 300 μm, and the porosity is 50-150 mesh, for example, 50, 60, 70, 80, 90, 100, 110, 120, 130, 140, 150 mesh. The polyphenylene sulfide support mesh plays an auxiliary role in helping to maintain the structural stability of the composite diaphragm. In one embodiment, the convex-concave structure of the surface layer of the composite diaphragm has a longitudinal cross-sectional shape selected from at least one of the following: continuous triangle, discontinuous triangle, discontinuous rectangle, continuous trapezoid, discontinuous trapezoid, continuous ellipse and discontinuous ellipse. The convex-concave structure is distributed in a regular lattice position or in an irregular random position on the surface layer.

[0025] In one embodiment, the height of each continuous triangle is 10-100 μm, preferably 30-80 μm, more preferably 50 μm; the base is 10-100 μm, preferably 30-80 μm, more preferably 50 μm; the ratio of the height to the base is 1:2-2:1, preferably 1:1. In one embodiment, the height of each non-continuous triangle is 10-100 μm, preferably 30-80 μm, more preferably 50 μm; the base is 10-100 μm, preferably 30-80 μm, more preferably 50 μm; the ratio of the height to the base is 1:2-2:1, preferably 1:1; the distance between two adjacent triangles is 10-100 μm, preferably 30-80 μm, more preferably 50 μm. In one embodiment, the height of each non-continuous rectangle is 10-100 μm, preferably 30-80 μm, more preferably 50 μm; the width is 10-100 μm, preferably 30-80 μm, more preferably 50 μm; the ratio of height to width is 1:2-2:1, preferably 1:1. In one embodiment, the height of each continuous trapezoid is 10-100 μm, preferably 30-80 μm, more preferably 50 μm; the upper base is 10-100 μm, preferably 20-80 μm, more preferably 30 μm, the lower base is 10-100 μm, preferably 20-80 μm, more preferably 70 μm, and the ratio of height to lower base is 1:2-2:1, preferably 1:1. In one embodiment, the height of each rectangle of the non-continuous trapezoid is 10-100 μm, preferably 30-80 μm, more preferably 50 μm; the upper base is 10-100 μm, preferably 20-80 μm, more preferably 30 μm, the lower base is 10-100 μm, preferably 20-80 μm, more preferably 70 μm, and the ratio of the height to the lower base is 1:2-2:1, preferably 1:1; the distance between two adjacent trapezoids is 10-100 μm, preferably 30-80 μm, more preferably 50 μm. In one embodiment, the short semi-axis of the continuous ellipse is 10-100 μm, preferably 30-80 μm, more preferably 50 μm; the long semi-axis is 10-100 μm, preferably 30-80 μm, more preferably 50 μm; the ratio of the short semi-axis to the long semi-axis is 1:2-2:1. In one embodiment, the short semi-axis of the discontinuous ellipse is 10 to 100 μm, preferably 30 to 80 μm, more preferably 50 μm; the long semi-axis is 10 to 100 μm, preferably 30 to 80 μm, more preferably 50 μm; the ratio of the short semi-axis to the long semi-axis is 1:2 to 2:1; the distance between two adjacent ellipses is 10 to 100 μm, preferably 30 to 80 μm, more preferably 50 μm. When the size of the convex-concave structure is within the above range, the surface-coated catalyst layer can be prevented from falling off during bending or shaking during the generation and use process, thereby improving the stability of the membrane electrode. At the same time, it can improve the electrolysis efficiency, reduce energy consumption, increase the current density, and reduce voltage loss.

[0026] In one embodiment, the surface resistance of the composite diaphragm is 0.1-0.4 ohm cm 2 @25°C 30 wt% KOH, e.g., 0.1, 0.15, 0.2, 0.25, 0.3, 0.35, or 0.4 ohm cm 2 @25℃ 30wt% KOH; bubble point pressure is 2~10bar, for example, 2, 3, 4, 5, 6, 7, 8, 910bar; hydrogen permeability is 1~25*10 –12 mol / (cm sec bar), e.g. 1, 5, 10, 15, 20, 25*10 –12 mol / (cm sec bar). In one embodiment, the first catalyst layer comprises a cathode catalyst, which is at least one selected from the following: platinum carbon, Raney nickel, nickel powder, cobalt powder, nickel molybdenum powder and nickel cobalt powder. In one embodiment, the cathode catalyst is Raney nickel. The above catalysts are all commonly used cathode catalysts in alkaline water electrolysis hydrogen production. In one embodiment, the second catalyst layer comprises an anode catalyst, which is at least one selected from the following: nickel hydroxide, cobalt hydroxide, iron hydroxide, nickel cobalt hydroxide, nickel iron hydroxide, cobalt iron hydroxide and nickel cobalt iron hydroxide. In one embodiment, the anode catalyst is nickel iron hydroxide; the above catalysts are all commonly used catalysts in alkaline water electrolysis hydrogen production. In one embodiment, the thickness of the first catalyst layer and the second catalyst layer is 10 to 30 μm, for example, 10, 15, 20, 25, 30 μm. When the thickness of the catalyst layer is within the above range, the catalytic effect can be fully provided, and the structural stability is ensured, and it will not fall off or deform due to being too thick or too thin.

[0027] In a specific embodiment, the composite membrane surface resistance is 0.3 ohm cm 2 @25℃ 30wt% KOH, bubble point pressure is 3bar, hydrogen permeability is 20*10 –12 mol / (cm sec bar); the first catalyst layer is a Raney nickel layer with a thickness of 25 μm; and the second catalyst layer is a nickel iron hydroxide layer with a thickness of 15 μm.

[0028] In a typical embodiment, the method for preparing any of the aforementioned membrane electrodes comprises the following steps:

[0029] (1) placing a substrate having a surface structure in a horizontal position, then placing a polyphenylene sulfide support net on the surface of the substrate, then coating the substrate with a composite membrane casting liquid to form a coated composite membrane casting liquid layer, the polyphenylene sulfide support net being immersed in the casting liquid layer, a first surface of the composite membrane casting liquid layer being in contact with the surface structure of the substrate to form a convex-concave structure, and a second surface opposite to the first surface being a plane;

[0030] (2) immersing the substrate coated with the composite diaphragm casting liquid layer in step (1) into a first phase inversion solution to perform a first phase inversion for a first time;

[0031] (3) turning the same substrate as in step (1) upside down on the second surface that has undergone the first phase transformation in step (2), and then performing a mechanical extrusion process to form a convex-concave structure on the second surface;

[0032] (4) removing the two substrates in step (3) to obtain a composite diaphragm embryo, placing the composite diaphragm embryo in a second phase transformation solution for a second phase transformation for a second time, thereby obtaining a composite diaphragm, and then rinsing the composite diaphragm with pure water;

[0033] (5) preparing a first catalyst slurry and a second catalyst slurry, uniformly coating the first catalyst slurry on the first surface of the composite membrane in step (4), uniformly coating the second catalyst slurry on the second surface of the composite membrane in step (4), and then drying for a second time to obtain a membrane electrode.

[0034] In one embodiment, the thickness of the polyphenylene sulfide support network in step (1) is 100-300 μm and the porosity is 50-150 meshes, preferably the thickness of the polyphenylene sulfide support network is 200 μm and the porosity is 100 meshes.

[0035] In one embodiment, the material of the substrate in step (1) is a rigid material or a plastic material. In a preferred embodiment, the rigid material is at least one selected from the following: sapphire, quartz, nickel, titanium, stainless steel and copper. In a preferred embodiment, the plastic material is at least one selected from the following: polytetrafluoroethylene, polypropylene and polyethylene terephthalate. The choice of the material of the substrate is within the capabilities of those skilled in the art, as long as it can achieve the desired surface structure and maintain the desired surface structure stable during production. In a preferred embodiment, the material of the substrate is polytetrafluoroethylene.

[0036] In one embodiment, the coating in step (1) is performed by slit coating. The method of slit coating is within the capabilities of those skilled in the art, as long as it can coat the composite diaphragm casting solution on the substrate with the desired size and thickness. Therefore, in a preferred embodiment, the gap of the slit is 200 to 1000 μm, preferably 300 to 800 μm, more preferably 400 to 700 μm, and most preferably 500 μm; the width of the slit is 20 to 200 cm, preferably 30 to 100 cm, more preferably 40 to 70 cm, and most preferably 50 cm; the coating line speed is 100 to 1000 mm / min, preferably 150 to 750 mm / min, and most preferably 200 mm / min; and the coating flow rate is 10 to 100 mL / min, preferably 15 to 50 mL / min, and more preferably 15 mL / min.

[0037] In one embodiment, the viscosity of the composite membrane casting liquid in step (1) is 10 to 1000 mPa.s, preferably 50 to 800 mPa.s, more preferably 100 to 500 mPa.s, and most preferably 200 mPa.s. The viscosity of the composite membrane casting liquid should be sufficient to maintain the structural stability of the coated composite membrane liquid layer, thereby avoiding deformation before the first phase transformation.

[0038] In one embodiment, the first phase inversion solution in step (2) is selected from any one of the following: pure water, ethanol, acetone, toluene, cyclohexene, ethylene glycol and chloroform, preferably pure water. The first phase inversion solution helps the coated composite diaphragm liquid layer to solidify for subsequent operations. In one embodiment, the first phase inversion time in step (2) is 0.1 to 10 minutes, preferably 1 minute. The first phase inversion time should be sufficient for the coated composite diaphragm liquid layer to solidify.

[0039] In one embodiment, the pressure of mechanical extrusion in step (3) is 0.1-1 MPa, preferably 0.15-0.5 MPa, and more preferably 0.2 MPa; the thickness of the film after extrusion is 100-500 μm, preferably 200-400 μm, and more preferably 300 μm. Mechanical extrusion is used to form a convex-concave structure on the second surface. If the pressure is too small, it is difficult to form a convex-concave structure corresponding to the first surface, and if the pressure is too large, it is easy to damage the composite diaphragm embryo. Therefore, controlling the pressure of mechanical extrusion within the aforementioned range and thereby obtaining a film thickness after extrusion within the aforementioned range helps to obtain a composite diaphragm embryo with a stable structure.

[0040] In one embodiment, the second phase inversion solution in step (4) is a mixed solution of an organic acid and an inorganic salt, the organic acid being at least one selected from the following: citric acid, fumaric acid, acetic acid, formic acid and tannic acid, preferably tannic acid or citric acid; the inorganic salt being at least one selected from the following: potassium sulfate, sodium sulfate, potassium nitrate, sodium nitrate, potassium chloride and sodium chloride, preferably sodium chloride or potassium chloride; the concentration of the organic acid is 0.001 to 1 mol / L, preferably 0.01 to 0.5 mol / L, more preferably 0.02 to 0.1 mol / L; the concentration of the inorganic salt is 0.01 to 1 mol / L, preferably 0.05 to 0.5 mol / L, more preferably 0.1 to 0.3 mol / L. The second phase inversion solution helps to form a stable porous structure inside the composite diaphragm. In one embodiment, the second time for the second phase inversion in step (4) is 5 to 120 min, preferably 30 to 90 min, more preferably 60 min. The time within the above range will contribute to the full completion of the second phase inversion. In one embodiment, the pure water rinse in step (4) is performed 1 to 5 times, preferably 3 times, so as to perform effective cleaning.

[0041] In one embodiment, the first catalyst slurry in step (5) comprises: (i) a cathode catalyst, which is at least one selected from the following: platinum carbon, Raney nickel, nickel powder, cobalt powder, nickel molybdenum powder and nickel cobalt powder, preferably Raney nickel; the content of the cathode catalyst is 1 to 100 mg / mL of the first catalyst slurry, preferably 10 to 80 mg / mL of the first catalyst slurry, more preferably 30 to 70 mg / mL of the first catalyst slurry, and most preferably 50 mg / mL of the first catalyst slurry; (ii) a dispersion liquid, which is ethanol and any one selected from the following in a ratio of 1:1 A mixture of n-butanol, isopropanol, turpentine, ethylene glycol, glycerol and tert-butanol in a volume ratio of 0 to 10:1, preferably a mixture of ethanol and turpentine in a volume ratio of 1:1; (iii) a viscosity modifier, which is an anion exchange resin, preferably any one selected from the following: polystyrene-based anion exchange resin, tetramethylammonium hydroxide-based resin, amino resin, polyvinyl chloride-based resin, more preferably amino resin; the amount of the viscosity modifier is 0.1 to 10 wt % of the mass of the cathode catalyst, preferably 1 to 5 wt %, more preferably 2 wt %.

[0042] In one embodiment, the second catalyst slurry in step (5) comprises: (i) an anode catalyst, which is at least one selected from the following: nickel hydroxide, cobalt hydroxide, iron hydroxide, nickel cobalt hydroxide, nickel iron hydroxide, cobalt iron hydroxide and nickel cobalt iron hydroxide, preferably nickel iron hydroxide; wherein the content of the anode catalyst is 1 to 100 mg / mL of the second catalyst slurry, preferably 10 to 80 mg / mL of the second catalyst slurry, more preferably 20 to 70 mg / mL of the first catalyst slurry, and most preferably 30 mg / mL of the second catalyst slurry; (ii) a dispersion liquid, which is ethanol and a dispersion liquid selected from the following: A mixture of any of the following items mixed in a volume ratio of 1:10 to 10:1: n-butanol, isopropanol, turpentine, ethylene glycol, glycerol and tert-butanol, preferably a mixture of ethanol and isopropanol mixed in a volume ratio of 2:1; and (iii) a viscosity modifier, which is an anion exchange resin, preferably any one selected from the following items: polystyrene-based anion exchange resin, tetramethylammonium hydroxide-based resin, amino resin, polyvinyl chloride-based resin, preferably amino resin; the amount of the viscosity modifier is 0.1 to 10 wt% of the mass of the anode catalyst, preferably 1 to 5 wt%, more preferably 2 wt%. The viscosity of the first catalyst slurry in step (5) is 100 to 200 mPa.s, preferably 110 to 150 mPa.s, more preferably 120 mPa.s; the viscosity of the second catalyst slurry is 100 to 200 mPa.s; preferably 100 mPa.s. The properties of the catalyst slurry are sufficient to ensure uniform coating of the catalyst on the composite diaphragm embryo body and to ensure that no undesirable deformation and aggregation occur before drying.

[0043] In a preferred embodiment, the gap of the slit of the slit coating in step (5) is 10 to 200 μm, preferably 20 to 100 μm, and more preferably 50 μm; the width of the slit is 20 to 200 cm, preferably 30 to 100 cm, and more preferably 40 cm; the linear speed is 50 to 200 mm / min, preferably 50 mm / min; and the flow rate is 1 to 20 mL / min, and preferably 5 mL / min.

[0044] In one embodiment, the drying in step (5) is carried out in a non-flowing inert gas environment, preferably the inert gas is at least one selected from the following: nitrogen, helium and argon, more preferably nitrogen; the humidity is 10-50% RH, preferably 25% RH; the drying temperature is 25-50° C., preferably 30-40° C., more preferably 37° C.; the second time is 6-24 hours, preferably 12 hours. The above conditions are sufficient to ensure that the catalyst layer is fully dried without undesired deformation and aggregation.

[0045] The present invention is further described in detail below in conjunction with specific embodiments. These embodiments should not be construed as limiting the scope of protection claimed by the present invention.

[0046] Embodiment 1:

[0047] This embodiment is carried out according to the following operation to prepare a membrane electrode coated with Raney nickel on one side and nickel iron hydroxide on the other side:

[0048] A polytetrafluoroethylene substrate with a continuous triangular (serrated) surface is placed in a horizontal position, each triangle is 50 μm high and 50 μm wide, and a polyphenylene sulfide support net is placed on the surface, with a mesh size of 100 and a thickness of 200 μm. Subsequently, a composite diaphragm casting liquid with a viscosity of 200 mPa.s is scraped on the substrate surface by slit coating and the polyphenylene sulfide support net is immersed, the slit gap is 500 μm, the slit width is 50 cm, the linear speed is 200 mm / min, and the flow rate is 15 mL / min;

[0049] The substrate with the film liquid layer on the surface was immersed in pure water for 1 min and then taken out;

[0050] The same substrate as in step (1) is placed upside down on the surface of step (2), and then subjected to mechanical extrusion treatment, the extrusion pressure is 0.2 MPa, and the film thickness after extrusion is 300 μm;

[0051] The two substrates in step (3) were removed, and the membrane material was placed in a mixed solution consisting of 0.02 mol / L tannic acid and 0.1 mol / L sodium chloride for 60 min, and then the surface solution was rinsed with pure water to obtain a composite diaphragm with a serrated surface;

[0052] A catalyst dispersion consisting of ethanol and turpentine in a volume ratio of 1:1 was prepared, and then Raney nickel was stirred and dispersed, the content of the catalyst added to the dispersion was 50 mg / mL, and amino resin was added in an amount of 2 wt% of the catalyst mass, and the slurry viscosity was 120 mpa.s;

[0053] A catalyst dispersion consisting of ethanol and isopropanol in a volume ratio of 2:1 was prepared, and then nickel iron hydroxide was stirred and dispersed, the content of the catalyst added to the dispersion was 30 mg / mL, and an amino resin was added in an amount of 2 wt% of the catalyst mass, and the slurry viscosity was 100 mpa.s;

[0054] The catalyst slurry was coated on both sides of the membrane in step (4) by slit coating, wherein the slit gap of the slit coating was 25 μm when coating on the cathode side and 15 μm when coating on the anode side; the slit width was 40 cm, the line speed was 50 mm / min, the flow rate was 5 mL / min, and the membrane electrode was formed by drying in a nitrogen environment with a humidity of 25% RH for 12 hours.

[0055] Embodiment 2:

[0056] The mixed solution consisting of 0.02 mol / L tannic acid and 0.1 mol / L sodium chloride in Example 1 was replaced by a mixed solution consisting of 0.05 mol / L citric acid and 0.2 mol / L potassium chloride, and the remaining steps were the same.

[0057] Comparative Example 1:

[0058] The membrane material used was a commercial Zirfon UTP 500 composite diaphragm, and the cathode and anode side catalysts were coated using the coating method in Example 1, wherein the cathode side catalyst was Raney nickel with a catalyst layer thickness of 150 μm, and the anode side catalyst was nickel iron hydroxide with a catalyst layer thickness of 50 μm.

[0059] Comparative Example 2:

[0060] The continuous triangular (serrated) polytetrafluoroethylene substrate in Example 1 was changed to a flat substrate, and the remaining steps were the same.

[0061] Test method:

[0062] The membrane electrode cut to a size of 5cm x 5cm was assembled to a single cell fixture, in which the cathode and anode gas diffusion layers were made of nickel felt with a porosity of 80%. During the test, the electrode clamps of the electrochemical workstation were clamped to the cathode and anode of the electrolyzer, 30% KOH solution was circulated at a flow rate of 100mL / min, the heating device was turned on, and the temperature was set to 90°C. The cell voltage of each sample at different current densities in the water electrolysis test was obtained, which represents the hydrogen production voltage value of a single electrolysis unit when a certain current density is reached. Therefore, the lower the value, the lower the energy consumption at the current density, and the higher the economic efficiency of the hydrogen production reaction.

[0063] Test results:

[0064] In Example 1, when the membrane electrode coated with Raney nickel and nickel iron hydroxide was used in an alkaline water electrolysis single cell test, the current reached 6000 A / m 2 The current density of the cell voltage is only 1.75V, and the DC power consumption is 4.18kWh / Nm 3In Example 2, 6000A / m was achieved in the electrolysis water test. 2 The current density of the cell voltage is 1.78V, and the DC power consumption is 4.25kWh / Nm 3 In Comparative Example 1, the electrolytic cell was operated at a current density of 2500 A / m 2 The DC power consumption is 4.5kWh / Nm 3 In comparative example 2, the electrolysis water test reached 6000A / m 2 The cell voltage of the current density is 1.92V, and the DC power consumption is 4.59kWh / Nm 3 .

[0065] In Example 1, the membrane electrode exhibits excellent performance in producing hydrogen by electrolysis of water. Meanwhile, after the water electrolysis test, the surface catalyst and the diaphragm still have good bonding strength.

[0066] Compared with Example 1, after the phase inversion solution is replaced in Example 2, the membrane material has a different internal pore structure and porosity, but the membrane electrode's performance in hydrogen production by electrolysis of water is still at a high level, indicating that the membrane electrode preparation method of the present invention is universal for membrane manufacturing processes; Comparative Example 1 uses a method of coating a catalyst on a commercial composite diaphragm. When the catalyst loading is high, the water electrolysis performance is not improved, and the surface catalytic layer is peeled off from the membrane material; the surface of the membrane material prepared in Comparative Example 2 does not have a serrated structure, and the effective catalytic activity area is lower under the same membrane electrode geometric area, so the performance is lower.

[0067] The results of the above embodiments show that the membrane electrode of the present invention includes a composite diaphragm with a convex-concave structure, and the catalyst layer is directly coated on the surface of the composite diaphragm to form a zero-gap structure. Due to the convex-concave structure, the catalyst layer coated on the surface can be prevented from falling off during bending or shaking during the production and use process, thereby improving the stability of the membrane electrode. At the same time, since the convex-concave structure increases the surface area of ​​the electrode, it can improve the electrolysis efficiency, reduce energy consumption, increase the current density, and reduce voltage loss. On the other hand, since the electrode is fitted to the diaphragm, the solution resistance between the two electrodes is greatly reduced, which not only allows a more compact structure to be obtained, but also further improves the high efficiency and safety of electrolysis.

Claims

1. A membrane electrode based on a composite diaphragm, comprising: Composite diaphragm; a first catalyst layer; and a second catalyst layer; The composite diaphragm has a base layer and a surface layer, the surface layer has a convex-concave structure, and the first catalyst layer and the second catalyst layer are uniformly coated on the surface layer of the composite diaphragm.

2. The membrane electrode according to claim 1, wherein: The thickness of the base layer of the composite diaphragm is 250-400 μm, and the base layer contains a polyphenylene sulfide support network, the thickness of the polyphenylene sulfide support network is 100-300 μm and the porosity is 50-150 mesh, preferably the thickness of the polyphenylene sulfide support network is 200 μm and the porosity is 100 mesh; The convex-concave structure of the surface layer of the composite separator has a longitudinal cross-sectional shape of at least one selected from the group consisting of continuous triangles, non-continuous triangles, non-continuous rectangles, continuous trapezoids, non-continuous trapezoids, continuous ellipses, non-continuous ellipses, and any combination thereof; The convex-concave structures are distributed on the surface layer in a regular lattice position or in an irregular random position, preferably in a regular lattice position.

3. The membrane electrode according to claim 2, wherein: The height of each of the continuous triangles is 10 to 100 μm, preferably 30 to 80 μm, more preferably 50 μm; the base is 10 to 100 μm, preferably 30 to 80 μm, more preferably 50 μm; the ratio of the height to the base is 1:2 to 2:1, preferably 1:1; The height of each of the non-continuous triangles is 10-100 μm, preferably 30-80 μm, more preferably 50 μm; the base is 10-100 μm, preferably 30-80 μm, more preferably 50 μm; the ratio of the height to the base is 1:2-2:1, preferably 1:1; the distance between two adjacent triangles is 10-100 μm, preferably 30-80 μm, more preferably 50 μm; The height of each of the non-continuous rectangles is 10 to 100 μm, preferably 30 to 80 μm, more preferably 50 μm; the width is 10 to 100 μm, preferably 30 to 80 μm, more preferably 50 μm; the ratio of the height to the width is 1:2 to 2:1, preferably 1:1; The height of each rectangle of the continuous trapezoid is 10-100 μm, preferably 30-80 μm, more preferably 50 μm; the upper base is 10-100 μm, preferably 20-80 μm, more preferably 30 μm, the lower base is 10-100 μm, preferably 20-80 μm, more preferably 70 μm, and the ratio of the height to the lower base is 1:2-2:1, preferably 1:1; The height of each rectangle of the non-continuous trapezoid is 10-100 μm, preferably 30-80 μm, more preferably 50 μm; the upper base is 10-100 μm, preferably 20-80 μm, more preferably 30 μm, the lower base is 10-100 μm, preferably 20-80 μm, more preferably 70 μm, and the ratio of the height to the lower base is 1:2-2:1, preferably 1:1; the distance between two adjacent trapezoids is 10-100 μm, preferably 30-80 μm, more preferably 50 μm; The short semi-axis of the continuous ellipse is 10 to 100 μm, preferably 30 to 80 μm, more preferably 50 μm; the long semi-axis is 10 to 100 μm, preferably 30 to 80 μm, more preferably 50 μm; the ratio of the short semi-axis to the long semi-axis is 1:2 to 2:1; and The short semi-axis of the non-continuous ellipse is 10 to 100 μm, preferably 30 to 80 μm, more preferably 50 μm; the long semi-axis is 10 to 100 μm, preferably 30 to 80 μm, more preferably 50 μm; the ratio of the short semi-axis to the long semi-axis is 1:2 to 2:1; the distance between two adjacent ellipses is 10 to 100 μm, preferably 30 to 80 μm, more preferably 50 μm.

4. The membrane electrode according to claim 1, wherein: The surface resistance of the composite diaphragm is 0.1 to 0.4 ohm cm 2 @25℃ 30wt% KOH, bubble point pressure is 2~10bar, hydrogen permeability is 1~25*10 –12 mol / (cm sec bar); The first catalyst layer comprises a cathode catalyst, which is at least one selected from the group consisting of platinum carbon, Raney nickel, nickel powder, cobalt powder, nickel molybdenum powder and nickel cobalt powder, preferably Raney nickel; and The second catalyst layer comprises an anode catalyst, which is at least one selected from the group consisting of nickel hydroxide, cobalt hydroxide, iron hydroxide, nickel cobalt hydroxide, nickel iron hydroxide, cobalt iron hydroxide and nickel cobalt iron hydroxide, preferably nickel iron hydroxide; wherein The thickness of the first catalyst layer and the second catalyst layer is 10 to 30 μm.

5. The membrane electrode according to claim 4, wherein: The surface resistance of the composite diaphragm is 0.3 ohm cm 2 @25℃ 30wt% KOH, bubble point pressure is 3bar, hydrogen permeability is 20*10 –12 mol / (cm sec bar); The first catalyst layer is a Raney nickel layer with a thickness of 25 μm; and The second catalyst layer is a nickel iron hydroxide layer with a thickness of 15 μm.

6. A method for preparing a membrane electrode according to any one of claims 1 to 5, wherein: The method comprises the following steps: (1) placing a substrate having a surface structure in a horizontal position, then placing a polyphenylene sulfide support net on the surface of the substrate, then coating the substrate with a composite membrane casting liquid to form a coated composite membrane casting liquid layer, wherein the polyphenylene sulfide support net is immersed in the casting liquid layer, wherein a first surface of the composite membrane casting liquid layer contacts the surface structure of the substrate to form the convex-concave structure, and a second surface opposite to the first surface is a plane; (2) immersing the substrate coated with the composite diaphragm casting liquid layer in step (1) into a first phase inversion solution to perform a first phase inversion for a first period of time; (3) flipping the same substrate as in step (1) on the second surface that has been subjected to the first phase transformation in step (2), and then performing a mechanical extrusion process, thereby forming the convex-concave structure on the second surface; (4) removing the two substrates in step (3) to obtain the composite membrane embryo, placing the composite membrane embryo in a second phase inversion solution for a second phase inversion for a second time, thereby obtaining the composite membrane, and then rinsing the composite membrane with pure water; (5) preparing a first catalyst slurry and a second catalyst slurry, uniformly coating the first catalyst slurry on the first surface of the composite membrane in step (4), uniformly coating the second catalyst slurry on the second surface of the composite membrane in step (4), and then drying for a second time to obtain the membrane electrode.

7. The method according to claim 6, wherein: The polyphenylene sulfide support network in step (1) has a thickness of 100 to 300 μm and a porosity of 50 to 150 meshes, preferably a thickness of 200 μm and a porosity of 100 meshes; The material of the substrate in step (1) is a rigid material or a plastic material. Preferably, the rigid material is at least one selected from the following: sapphire, quartz, nickel, titanium, stainless steel and copper; the plastic material is at least one selected from the following: polytetrafluoroethylene, polypropylene and polyethylene terephthalate; preferably, the material of the substrate is polytetrafluoroethylene; The coating in step (1) is carried out by slit coating, the gap of the slit is 200-1000 μm, preferably 300-800 μm, more preferably 400-700 μm, most preferably 500 μm; the width of the slit is 20-200 cm, preferably 30-100 cm, more preferably 40-70 cm, most preferably 50 cm; the linear speed of the coating is 100-1000 mm / min, preferably 150-750 mm / min, most preferably 200 mm / min; and the flow rate of the coating is 10-100 mL / min, preferably 15-50 mL / min, more preferably 15 mL / min; The viscosity of the composite diaphragm casting solution in step (1) is 10 to 1000 mPa.s, preferably 50 to 800 mPa.s, more preferably 100 to 500 mPa.s, and most preferably 200 mPa.s.

8. The method according to claim 6, wherein: The first phase inversion solution in step (2) is selected from any one of the following: purified water, ethanol, acetone, toluene, cyclohexene, ethylene glycol and chloroform, preferably purified water; The first phase conversion time in step (2) is 0.1 to 10 min, preferably 1 min.

9. The method according to claim 6, wherein: The mechanical extrusion pressure in step (3) is 0.1-1 MPa, preferably 0.15-0.5 MPa, and more preferably 0.2 MPa; the film thickness after extrusion is 100-500 μm, preferably 200-400 μm, and more preferably 300 μm.

10. The method according to claim 6, wherein: The second phase inversion solution in step (4) is a mixed solution of an organic acid and an inorganic salt, wherein the organic acid is at least one selected from the following: citric acid, fumaric acid, acetic acid, formic acid and tannic acid, preferably tannic acid or citric acid; the inorganic salt is at least one selected from the following: potassium sulfate, sodium sulfate, potassium nitrate, sodium nitrate, potassium chloride and sodium chloride, preferably sodium chloride or potassium chloride; the concentration of the organic acid is 0.001 to 1 mol / L, preferably 0.01 to 0.5 mol / L, more preferably 0.02 to 0.1 mol / L; the concentration of the inorganic salt is 0.01 to 1 mol / L, preferably 0.05 to 0.5 mol / L, more preferably 0.1 to 0.3 mol / L; The second time in step (4) is 5 to 120 min, preferably 30 to 90 min, and more preferably 60 min; The pure water washing in step (4) is performed 1 to 5 times, preferably 3 times.

11. The method according to claim 6, wherein: The first catalyst slurry in step (5) comprises: (i) a cathode catalyst, which is at least one selected from the following: platinum carbon, Raney nickel, nickel powder, cobalt powder, nickel molybdenum powder and nickel cobalt powder, preferably Raney nickel; the content of the cathode catalyst is 1-100 mg / mL of the first catalyst slurry, preferably 10-80 mg / mL of the first catalyst slurry, more preferably 30-70 mg / mL of the first catalyst slurry, and most preferably 50 mg / mL of the first catalyst slurry; (ii) a dispersion liquid, which is a mixture of ethanol and any one selected from the following: n-butanol, isopropanol, turpentine, ethylene glycol, glycerol and tert-butanol in a volume ratio of 1:10 to 10:1, preferably a mixture of ethanol and turpentine in a volume ratio of 1:1; (iii) a viscosity modifier, which is an anion exchange resin, preferably any one selected from the following: Polystyrene-based anion exchange resin, tetramethylammonium hydroxide-based resin, amino resin, polyvinyl chloride-based resin, more preferably amino resin; the amount of the viscosity modifier is 0.1-10wt% of the mass of the cathode catalyst, preferably 1-5wt%, more preferably 2wt%; The second catalyst slurry in step (5) comprises: (i) an anode catalyst, which is at least one selected from the following: nickel hydroxide, cobalt hydroxide, iron hydroxide, nickel cobalt hydroxide, nickel iron hydroxide, cobalt iron hydroxide and nickel cobalt iron hydroxide, preferably nickel iron hydroxide; wherein the content of the anode catalyst is 1-100 mg / mL of the second catalyst slurry, preferably 10-80 mg / mL of the second catalyst slurry, more preferably 20-70 mg / mL of the first catalyst slurry, and most preferably 30 mg / mL of the second catalyst slurry; (ii) a dispersion liquid which is a mixture of ethanol and any one selected from the group consisting of n-butanol, isopropanol, turpentine, ethylene glycol, glycerol and tert-butanol in a volume ratio of 1:10 to 10:1, preferably a mixture of ethanol and isopropanol in a volume ratio of 2:1; and (iii) a viscosity modifier, which is an anion exchange resin, preferably any one selected from the following: Polystyrene-based anion exchange resin, tetramethylammonium hydroxide-based resin, amino resin, polyvinyl chloride-based resin, preferably amino resin; the amount of the viscosity modifier is 0.1-10wt% of the mass of the anode catalyst, preferably 1-5wt%, more preferably 2wt%; The viscosity of the first catalyst slurry in step (5) is 100-200 mpa.s, preferably 110-150 mpa.s, more preferably 120 mpa.s; the viscosity of the second catalyst slurry is 100-200 mpa.s, preferably 100 mpa.s; The gap of the slit coating in step (5) is 10 to 200 μm, preferably 20 to 100 μm, and more preferably 50 μm; the width of the slit is 20 to 200 cm, preferably 30 to 100 cm, and more preferably 40 cm; the line speed is 50 to 200 mm / min, preferably 50 mm / min; the flow rate is 1 to 20 mL / min, and preferably 5 mL / min; The drying in step (5) is carried out in a non-flowing inert gas environment, and preferably the inert gas is at least one selected from the following: nitrogen, helium and argon, more preferably nitrogen; the humidity is 10-50% RH, preferably 25% RH; the drying temperature is 25-50°C, preferably 30-40°C, more preferably 37°C; the second time is 6-24h, preferably 12h.

12. Use of the membrane electrode according to any one of claims 1 to 5 in an alkaline water electrolysis system.